2020
DOI: 10.1002/cti2.1230
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D and MICA/B shedding: a ‘tag game’ between NK cells and malignant cells

Abstract: Natural killer (NK) cells are innate lymphocytes with cytotoxic functions and recognise target cells with the NK group 2D (NKG2D) receptor. Tumor cells are marked for NK‐cell‐mediated destruction upon expression of MICA and MICB (MICA/B), which are NKG2D ligands upregulated by many human cancers in response to cellular stress pathways associated with malignant transformation such as DNA damage and accumulation of misfolded proteins. However, MICA/B proteins are downregulated by tumor cells via intriguing molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 61 publications
0
42
0
1
Order By: Relevance
“…In addition, the involvement of MICA/B activation proteins was recently reported to impact on anti-tumor activity of NK cell [ 25 ]. Therefore, the extent of CD95, DR4, DR5, MICA/B expression alterations were then determined after cordycepin treatment for 24 h in either mRNA or protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the involvement of MICA/B activation proteins was recently reported to impact on anti-tumor activity of NK cell [ 25 ]. Therefore, the extent of CD95, DR4, DR5, MICA/B expression alterations were then determined after cordycepin treatment for 24 h in either mRNA or protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…This degradation causes tumor progression, biological functions, and an immunomodulatory response. Various studies have shown that the shedding of MICA on the surface of tumor cells is increased by proteases, including metalloproteinases (MMPs) and a disintegrin and metalloproteases (ADAMs) [42]. For instance, the overexpression of MMP-2 on the surface of renal cell carcinoma and membrane-type MMP-14 activity directly led to MICA shedding [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MHC class I-related chain molecules A and B (MICA and MICB) and natural cytotoxicity triggering receptor 3 ligand 1 (NR3LG1), also referred to B7-H6, are widely expressed by tumor cells (50,51), and they have been reported to be substrates of ADAM17 (52)(53)(54)(55). MICA/B and NR3LG1 are ligands of the NK cell activating receptor NKG2D and NKp30, respectively, and blocking their shedding increased tumor cell killing by NK cells (55,56). The above findings reveal that ADAM17's impact on NK cells is diverse (e.g., effector functions, proliferation, and trafficking) and multifactorial, thus addressing the effects of its inhibition on their function, especially in vivo, is complex.…”
Section: Discussionmentioning
confidence: 99%